An annotated checklist of species in the family Lagenophryidae (Ciliophora, Oligohymenophorea, Peritrichia), With a brief review of their taxonomy, morphology, and biogeography - Mayén-Estrada, Rosaura; Clamp, John C. (Zootaxa, 2016)
The genera Lagenophrys Stein, 1852, Paralagenophrys Clamp, 1987, Clistolagenophrys Clamp, 1991, and Operculigera Kane, 1969 make up the family Lagenophryidae and, together, contain more than 80 species worldwide that live mainly as ectosymbionts of crustaceans. Lagenophryids are characterized by possession of a lorica, but the lorica aperture and the associated parts of the body differ between genera. Despite their widespread distribution, relatively few papers have been published on lagenophryids in recent years, and the present paper is intended to promote research on lagenophryids by providing an annotated checklist of all known species and a brief review of the family, including data of their geographic distribution and their hosts.